Heterogeneity Of Pedagogical Practices In Competency-Based Economics Teaching: Discourse Analysis Of Public School Teachers In The Digital Economy Era - Gilang Aulia Prasetya; Sita Ratnaningsih (Jurnal Manajemen Pendidikan Islam Darussalam, 2026)
The digital economy era demands that economics teaching in high schools transform from a lecture-based approach to competency-based learning that is contextualized to the technology-based workplace. This study aims to analyze the heterogeneity of pedagogical practices in competency-based economics teaching through the discourses of three Economics teachers at SMAN 1 Tangerang Selatan in the digital economy era. The study used a qualitative approach with a case study design, involving three purposively selected teachers. Data were obtained through semi-structured interviews, a review of lesson plans/assets (RPP/ATP) and learning media, and descriptive notes on learning practices. The results indicate three main patterns of pedagogical practices: a conventional lecture-memorization-based pattern, an innovative digital pattern integrating e-commerce simulations and financial applications, and a hybrid pattern combining elements of both. The discussion shows that this heterogeneity is influenced by teaching experience, understanding of competency-based curriculum, and the availability of ICT infrastructure, and is in line with the TPACK framework and the findings of several previous studies. It is concluded that the variation in practices reflects teachers' negotiation process between traditional learning norms and the demands of digital transformation. This study's recommendations emphasize the importance of TPACK-based professional development programs and cross-school follow-up studies to strengthen the implementation of competency-based economics learning in the digital era.